Our Invited Essay Series: "Critical Engagements with the Politics of 'Extremism' and Schooling". Issue 2 (3rd April 2017) - Shirazi, Roozbeh
ABSTRACT: This issue of Diaspora, Indigenous, and Minority Education features two essays responding to Adeela Arshad-Ayaz and M. Ayaz Naseem''s lead article for this series, "Creating "Invited" Spaces for Counter-Radicalization and Counter-Extremism Education." Drawing upon metaphor and empirical research, these essays impart important theoretical tools for scholars who work on questions of migration, social justice, belonging, and security in education.